2021
DOI: 10.3389/fpsyt.2021.728278
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Most Closely Associated With Mood Disorders in Adolescents During the COVID-19 Pandemic? A Cross-Sectional Study Based on 1,771 Adolescents in Shandong Province, China

Abstract: Background and Aims: COVID-19 has been proven to harm adolescents' mental health, and several psychological influence factors have been proposed. However, the importance of these factors in the development of mood disorders in adolescents during the pandemic still eludes researchers, and practical strategies for mental health education are limited.Methods: We constructed a sample of 1,771 adolescents from three junior high middle schools, three senior high middle schools, and three independent universities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 59 publications
(60 reference statements)
1
38
0
Order By: Relevance
“…In this context, it was possible to support the idea that good SLP is inversely associated with higher levels of depression ( 40 ). In contrast, poor SLP can be considered one of the most significant risk factors for mood disorders during the COVID-19 pandemic ( 70 ). Lee et al ( 71 ) also emphasized that individuals with poor SLP are more likely to have some or severe problems not only with depression or anxiety, but also with physical activity, self-control and daily activity, and this may be reflected in an impaired quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was possible to support the idea that good SLP is inversely associated with higher levels of depression ( 40 ). In contrast, poor SLP can be considered one of the most significant risk factors for mood disorders during the COVID-19 pandemic ( 70 ). Lee et al ( 71 ) also emphasized that individuals with poor SLP are more likely to have some or severe problems not only with depression or anxiety, but also with physical activity, self-control and daily activity, and this may be reflected in an impaired quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents who are at a critical stage of cognitive development, the COVID-19 epidemic easily leads to various negative emotions and mental disorders. For example, Ren et al ( 2021 ) implemented a study with the sample of 1771 adolescents from junior high middle school, senior high middle school, and university in China and found that symptoms of anxiety and depression were 28.3 and 30.8% among the participants. Of course, this phenomenon of adolescents showing negative emotions during the COVID-19 epidemic also exists in American college students (Kecojevic et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above discussion, a large number of studies have explored the emotional experience of adolescents (Ren et al, 2021 ) at different academic stages, such as children (Shorer & Leibovich, 2020 ) and college students (Charles et al, 2021 ) during the COVID-19 pandemic, and it also includes follow-up studies of Liang et al ( 2021 ) and Li et al ( 2021 ). At the same time, some studies have even found the correlation between the adolescents’ emotional experience and their risk perception during the epidemic (Li et al, 2020a ), but they did not reveal whether there are causal relationships between the risk perception and emotions for the adolescents at different academic stages.…”
Section: Introductionmentioning
confidence: 99%
“… 9 A second study performed in China supported these results and demonstrated through survey use that out of 1771 adolescents, 28.3% experienced anxious symptoms and 30.8% experienced depressive symptoms. 10 Additionally, studies in the UK have shown that there has been an increase in depressive symptoms by 75% among children in assessments taken before and during lockdown. 11 Symptoms of anxiety also increased during quarantine.…”
Section: Methodsmentioning
confidence: 99%